Cognitive functions of women diagnosed with breast cancer in adjuvant chemotherapeutic treatment: a scope review - Mello, Tainara de Lima; Kupske, Juliedy Waldow; Zanella, Janice de Fátima Pavan; Schneider, Ione Jayce Ceola; Krug, Universidade de Cruz Alta (Unicruz) (Pensando Psicología, 2021)
Objective: To review subsidies on the neuropsychological profile of women with breast cancer undergoing chemotherapy.Methodology: This was a scope review based on a survey of the last five years in the PubMed, Scielo and Lilacs databases. The parameters proposed by PRISMA were followed and the following descriptors were used: “breast cancer/breast neoplasms” and “neuropsychological evaluation/ neuropsychological evaluation”.Results: 8 articles were found. Self-reports of cognitive impairment are still higher compared to results obtai-ned through neuropsychological instruments, however, the cognitive deficits presented with greater intensity refer to executive functions, memory, attention and processing speed.Conclusions: There is no consensus on the impact of cancer treatment (chemotherapy) on cognition, and there should be standardization of the assessment instruments, as well as the implementation of new neuroimaging technologies.